The formulation and evaluation of antiviral herbal tablet Chun-7 - Boldsaikhan, Munkhzaya; Jagar, Nomin; Battulga, Sugarmaa; Borbaatar, Battulga; Gantur, Ganchimeg; Ryenchindorj, Lkhaasuren; Daramzav, Otgonsuren; Soyollkham, Badamtsetseg (Journal of Eastern – Western Pharmacology and Pharmacy, 2025)
This study explores the formulation and evaluation of Chun-7 antiviral herbal tablets derived from a traditional Mongolian medicinal blend. The objective was to develop a tablet form to enhance the convenience and efficacy of Chun-7, traditionally used for respiratory tract viral infections. The Chun-7 formulation includes seven medicinal plants known for their pharmacological properties. Tablets were prepared using the wet granulation method, with granules adjusted to different moisture levels (2%, 4%, 6%, and 8%) to evaluate their impact on tablet characteristics. The tablets were assessed for weight variation, hardness, friability, and disintegration time. Results indicated that the maximum weight variation was 3.62%, within acceptable limits. Tablets with 5% and 6% granule moisture content exhibited optimal hardness (1.11 and 1.08 MPa, respectively) and acceptable friability. The qualitative and quantitative analysis methods were modified, and requirements were evaluated according to Mongolian National Pharmacopoeia. Total alkaloids and phenolic content were 1.2 mg and 8 mg, respectively. The study underscores the importance of moisture content in granule preparation, influencing the tablets’ physical, chemical, and mechanical properties. This research provides a viable alternative to traditional herbal powder formulations, enhancing dosage accuracy and patient compliance. Further studies are recommended to evaluate the clinical efficacy and long term stability of Chun-7 tablets under varied storage conditions.